Association of peptidoglycan recognition protein 1 to post‐myocardial infarction and periodontal inflammation: A subgroup report from the PAROKRANK (Periodontal Disease and the Relation to Myocardial Infarction) study. Issue 9 (19th July 2022) - Rathnayake, Nilminie; Gustafsson, Anders; Sorsa, Timo; Norhammar, Anna; Bostanci, Nagihan; ,
Abstract: Background: Peptidoglycan recognition protein 1 (PGLYRP1) is an antimicrobial and proinflammatory innate immunity protein activated during infections. We aimed to investigate whether PGYLRP1 and associated molecules of the immune response in saliva is a cumulative outcome result of both MI and periodontal inflammation. Methods and Results: Two hundred patients with MI and another 200 matched non‐MI controls were included. A full‐mouthexamination was conducted to assess periodontal inflammation and collection of stimulated saliva was performed 6 to 10 weeks after the first MI. PGLYRP1, triggering receptor expressed on myeloid cells 1 (TREM‐1), interleukin‐1 beta (IL‐1β) were analyzed by ELISA. Matrix metalloproteinase (MMP)‐8 levels were determined by IFMA. Compared to controls, MI patients showed higher salivary PGLYRP1, but not TREM‐1 levels. The difference in PGLYRP1 levels remained after adjustment for covariates. In MI patients, the PGLYRP1 levels positively correlated with BOP and PPD 4 to 5 mm. Among non‐MI subjects, the levels of PGLYRP1 correlated positively and significantly with BOP and total PPD. Salivary PGLYRP1 concentrations also showed strong positive correlations with levels of TREM‐1, IL‐1β and MMP‐8. In multivariate linear regression analysis, in MI patients, BOP and former smokingstatus displayed an association with salivary PGLYRP1 concentration. Conclusion: MI patients showed higher salivary PGLYRP1 levels than healthy controls, also after adjusting for smoking, sex, age and periodontal health status. Salivary levels of PGLYRP1 may reflect the overall inflammatory burden to chronic bacterial exposure, possibly underpinning the observed associations between periodontitis and exposure with MI.